Rapid Assessment of Clinical Information Systems in the Healthcare Setting - McMullen, C. K.; Ash, J. S.; Sittig, D. F.; Bunce, A.; Guappone, K.; Dykstra, R.; Carpenter, J.; Richardson, J.; Wright, A. (Methods of Information in Medicine, 2011)
Objective: Recent legislation in the United States provides strong incentives for implementation of electronic health records (EHRs). The ensuing transformation in U. S. health care will increase demand for new methods to evaluate clinical informatics interventions. Timeline constraints and a rapidly changing environment will make traditional evaluation techniques burdensome. This paper describes an anthropological approach that provides a fast and flexible way to evaluate clinical information systems.Methods: Adapting mixed-method evaluation approaches from anthropology, we describe a rapid assessment process (RAP) for assessing clinical informatics interventions in health care that we developed and used during seven site visits to diverse community hospitals and primary care settings in the U. S.Setting: Our multidisciplinary team used RAP to evaluate factors that either encouraged people to use clinical decision support (CDS) systems or interfered with use of these systems in settings ranging from large urban hospitals to single-practitioner, private family practices in small towns.Results: Critical elements of the method include: 1) developing a fieldwork guide; 2) carefully selecting observation sites and participants; 3) thoroughly preparing for site visits; 4) partnering with local collaborators; 5) collecting robust data by using multiple researchers and methods; and 6) analyzing and reporting data in a structured manner helpful to the oraganizations being evaluated.Conclusions: RAP, iteratively developed over the course of visits to seven clinical sites across the U.S., has succeeded in allowing a multidisciplinary team of informatics researchers to plan, gather and analyze data, and report results in a maximally efficient manner.
Keywords: Ethnography; qualitative methods; clinical informatics; healthcare evaluation mechanisms; computerized medical record systems